Superiority of CuSe as a non-nobel electrocatalyst among copper chalcogens for overall water splitting reactions - Mousumi Mondal; Sabyasachi Maity; Anirban Ghosh; Sujit Kumar Ghosh; Swapan Kumar Bhattacharya (Energy Nexus, 2024)
Among the transition metals copper is one of the cheapest earth- abandoned elements which can enhance electrocatalytic activity. The Cu-based catalysts are superior for catalytic performance and stability in alkaline media for oxygen evolution reaction (OER) and exhibit high activity in acidic media for hydrogen evolution reaction (HER).Synthesized CuSe nanoparticle is found as the most efficient bifunctional electrocatalyst among the synthesized Cu chalcogenides for water splitting reaction. Electrocatalytic performance for water oxidation was investigated in alkaline solution1(M) KOH for OER and 0.5 (M) H2SO4 for HER. To achieve 10 mA/cm2, it was observed an over potential (mV) of 343 for OER and 126 for HER, which are much smaller than these of CuS (385,320) and CuO (410, 345) studied. In this article, we have elucidated some essential criteria need to be specified to evaluate the water splitting performance including onset potential, overpotential, Tafel slope, turnover frequency (TOF), and stability of the copper chalcogenide nanoparticles.